2010
DOI: 10.1177/1091581809359708
|View full text |Cite
|
Sign up to set email alerts
|

Cannabinoid Receptor Agonist WIN-55,212-2 Protects Differentiated PC12 Cells From Organophosphorus- Induced Apoptosis

Abstract: Cannabinoid neuroprotection is usually greater in vivo than in neuronal cell culture systems. To the authors' knowledge, a good in vitro culture model for the neuroprotective effects of cannabinoids does not exist. Therefore, a 3-dimensional (3D) culture system was developed to investigate the neuroprotective effects of the cannabinoid receptor agonist WIN-55,212-2 on apoptosis of differentiated PC12 cells, caused by the organophosphorus compounds paraoxon and diazinon. Cells pretreated with WIN-55,212-2 were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 40 publications
(55 reference statements)
1
5
0
Order By: Relevance
“…The role of direct ACEA-dependent CB1 receptor activation in neuroprotection is confirmed by our finding that CB1 receptor antagonist AM251 significantly decreased cell viability and CB1 receptor expression induced by ACEA in PC12 cells treated with POX. Consistent with these results are our previous studies which have shown that cannabinoid receptor agonist WIN-55,212-2 protects differentiated PC12 cells from organophosphorus-induced apoptosis [43] and that stimulation of CB1 cannabinoid and NMDA receptors increases neuroprotective effect against diazinon-induced neurotoxicity [44].…”
Section: Resultssupporting
confidence: 90%
“…The role of direct ACEA-dependent CB1 receptor activation in neuroprotection is confirmed by our finding that CB1 receptor antagonist AM251 significantly decreased cell viability and CB1 receptor expression induced by ACEA in PC12 cells treated with POX. Consistent with these results are our previous studies which have shown that cannabinoid receptor agonist WIN-55,212-2 protects differentiated PC12 cells from organophosphorus-induced apoptosis [43] and that stimulation of CB1 cannabinoid and NMDA receptors increases neuroprotective effect against diazinon-induced neurotoxicity [44].…”
Section: Resultssupporting
confidence: 90%
“…Diazinon in the 200 µM dose decreased cell survival and CB1 receptor expression after 48 h-long exposure. In our earlier works with OPs, we found that sublethal concentrations of diazinon inhibited the outgrowth of axon-like processes and induced apoptosis of differentiated PC12 cells [4,18]. Other researchers also reported that diazoxon inhibited AChE activity and reduced transcripts of the α4 and β2 subunits of nAChRs (at the mRNA level) in PC12 cells [2].…”
Section: Discussionmentioning
confidence: 59%
“…AM251 did not decrease the viability and CB1 receptor expression increased by WIN55,212-2 in PC12 cells. However, in our previous work where PC12 cells were differentiated under the action of neural growth factor (NGF), AM251 inhibited the neuroprotective effect of WIN55,212-2 [4]. Hence, the reason for this disparity seems to be related to the cell differentiation process.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…These studies point in different directions showing both pro and antiapoptotic effects, depending on experimental system, cannabinoid type and dose. A recent study using R(+)WIN55,212-2, however, found that this cannabinoid inhibits apoptosis in PC12 cells (Sadri, Bahrami, Khazaei, Hashemi, & Asgari, 2010).…”
Section: Introductionmentioning
confidence: 98%